Chromatographic identification and spectrophotometric determination of a diuretic alkaloid in the roots of catharantus roseus (apocynaceae) an antihypertensive plant used in Benin - Agbodjogbé, Kpèdétin Wilfrid Dieu-Donné; SANNI, IMOROU; Bambola, Bouraïma; Kassehin, C. Urbain; Agossa, Sendip Ferman; Avoce, Charlotte; Etekpo, Tobi Noé (My University, 2022)
Arterial hypertension (AHT) remains a major public health problem because for its high frequency and its cardiovascular complications. Catharantus roseus (L.) G. Don (Apocynaceae) is one of the plants used in Benin for the traditional treatment of ypertension.The general objective of this work is to contribute to the management of arterial hypertension by identifying and determining the active principle of furosemide from the extract of the roots of Catharantus roseus (L.) G. Don.The extract was prepared using the method of maceration with distilled water in the proportions 1 m/10v. The extract obtained was used for the extraction of total alkaloids in basic medium with an aprotic polar solvent such as dichloromethane. Furosemide, one of the diuretics frequently used in the clinical center, was identified in the alkaloid extract by the method of analytical thin layer chromatography. The determination of the active principle of rosemide was made by UV-vis spectrophotometry at 276 nm. The yield of the crude aqueous extraction was 12.57%. Thin layer chromatography of the extract showed a spot at the same Rf as that of furosemide which is an alkaloid. The content of furosemide in the extract is1.27 ± 0.03 µg/g of extract.
Keywords: Arterial Hypertension; Catharantus; Roseus; Diuretic; Furosemide